Glomerular Lipidosis in Dogs. (September 2017) - Kohnken, Rebecca A.; Amerman, Hayley; Brown, Cathy A.; Furrow, Eva; Lees, George E.; Cianciolo, Rachel E.
Glomerular lipidosis (GL) is characterized by dilated glomerular capillary loops containing lipid-laden cells (foam cells). Previously, GL was considered to be an incidental finding because affected dogs were typically not azotemic. However, the International Renal Interest Society staging system for canine chronic kidney disease has increased the awareness of other clinical parameters (eg, proteinuria and hypertension) that should be included in the assessment of renal function. As such, the aim of this study was to determine clinical abnormalities and concurrent renal lesions in dogs with GL. GL was identified in renal biopsies from 46 dogs evaluated by the International Veterinary Renal Pathology Service. GL was the sole diagnosis in 5 of 46 cases (11%), all of which were proteinuric. All 5 dogs had at least 1 additional clinicopathologic abnormality consistent with renal disease, including hypertension (4), azotemia (3), and/or hypoalbuminemia (2). The remaining 41 dogs had GL in combination with other glomerular lesions, the most common being focal segmental glomerulosclerosis (16, 35%), lesions consistent with juvenile nephropathy (8, 17%), and glomerular amyloidosis (5, 11%). Overall, dogs with severe GL were younger than were those with mild GL ( P < .001). The percentage of glomeruli affected by GL differed by concurrent diagnoses ( P = .034), with the highest percentage of affected glomeruli in dogs with GL alone or those with concurrent juvenile nephropathy. These findings suggest that GL should be a recognized histologic phenotype of glomerular injury associated with clinical renal dysfunction and/or juvenile nephropathies.